Syura Sebagai Basis Etis Politik Islam - Muhammad Rizky HK (Politea : Jurnal Politik Islam, 2022)
This article tries to examine explore the concept of shura and its relevance to the Islamic Political Thought. In order to discuss this issue, the main focus will be directed on two main discussions; The ground concepts of Islamic Political Thought, and The Islamic concepts: shura (consultation) It is already known that shura concepts has been widely interpreted as a theoretical basis for electoral democracy in Islam. The main purpose is to present a more philosopical view of Islamic political thought throught it ethical basis and to show that there are and possibilities for an enrichment the discourse on Islamic political though with ethical concept within Islamic dogma.